Computer Aided Ergonomics: Evaluation Study of a Interaction Model for Digital Human Models. (May 2022) - Wolf, A.; Fackler, K.; Reulbach, M.; Wartzack, S.; Miehling, J.
Abstract: In user-centred design, digital human models hold the potential for proactive evaluations of ergonomics or discomfort in terms of a computer aided ergonomics tool. Therefore, models predicting human interaction behaviour, are necessary. In this contribution we present such a model as well as its initial evaluation. The evaluation is performed by applying the interaction model to a specific use case, conducting a comparison with an empirical subject study. The evaluation shows that similar and realistic human behaviour was predicted, which was consistent in terms of whole-body strain.